Purification, characterization, and complement fixation activity of acidic polysaccharides from Tuber sinoaestivum. (November 2017) - Li, Xiaolin; Zhang, Bo; Li, Juan; Zhou, Jie; He, Xiaolan; Ye, Lei; Zou, Jie; Wu, Chenguang; Zhang, Xiaoping; Peng, Weihong
Abstract: Tuber sinoaestivum, Chinese black truffle, which is very commercially important in China, is not only well known for its delicious taste but also for its high medical value. Polysaccharides from its European sister species Tuber aestivum have been shown to have some interesting bioactivities, but very few studies have been performed on it. In this study, 2 acidic polysaccharides, T. sinoaestivum polysaccharide-I (TSP-I) and T. sinoaestivum polysaccharide-II (TSP-II), were obtained from 100 °C water extracts of T. sinoaestivum fruiting bodies by diethylaminoethyl (DEAE) anion exchange chromatography and gel filtration. The polysaccharides presented similar monosaccharide composition, molecular size, and types of linkage. The results from methylation, Fourier transform infrared spectroscopy (FT-IR), and nuclear magnetic resonance (NMR) indicated the polysaccharides as the rhamno-mannan-like types that also contain mannuronic acid and acetyl groups. Both of TSP-I and TSP-II exhibited potential complement fixation activity. The higher molecular weight and lower amount of glucose in TSP-II may explain why it had higher complement fixation activity. Accordingly, the Chinese truffle T. sinoaestivum might serve as a potential immunomodulator. Highlights: Two rhamno-mannan like polysaccharides were purified from Tuber sinoaestivum. Structural elucidation was performed by GC, GC-MS, FT-IR and NMR. These two polysaccharides could be used as potential natural immunomodulators.